Antioxidant Compounds of the Edible Mushroom Pleurotus ostreatus - Enshasy, Hesham Ali El-; Selvamani, Shanmugaprakasham; Dailin, Daniel Joe; Malek, Roslinda Abd; Hanapi, Siti Zulaiha; Ambehabati, Kugan Kumar; Sukmawati, Dalia; Leng, Ong Mei; Moloi, Neo (International Journal of Biotechnology for Wellness Industries, 2018)
Mushrooms have been used since centuries in many ancient cultures as source of food and medicine. However, until now the therapeutic values of mushrooms position this group of macrofungi as one of the major component in traditional medicine practice especially in South East Asia and China. Of different species of known mushrooms, Pleurotus spp. is widely known as part of food chain based on its high nutritional value. However, of the more than 70 species known, only few species are cultivated in mass production and used such as P. ostreatus, P. florida, and P. ajor-caju. However, P. ostreatus (widely known as oyster mushroom) received more attention in food industries based on its high growth rate and ease of cultivation using different substrates. This mushroom is rich of wide range of bioactive molecules of proven medicinal values with many therapeutic activities as anticancer, immunomodulatory, antiapoptotic, anti hypocholesterolemic, anti hyperglycemic, antimicrobial, anti-inflammatory, anti-osteoporetic, and many others. This work focuses on reviewing on the different classes of oyster mushroom bioactive compounds of antioxidant activities such as phenolics, beta carotene, lycopene, ascorbic acid, tocopherols, and ergosterols. This review provides also comprehensive information on the recent research to enhance the antioxidant properties through alteration of the cultivation strategy and addition of some compounds during the cultivation of P. ostreatus.